Pulchinenoside B4 exerts the protective effects against cisplatin-induced nephrotoxicity through NF-κB and MAPK mediated apoptosis signaling pathways in mice. (1st November 2020) - Wang, Shuang; Tang, Shan; Chen, Xuan; Li, Xin; Jiang, Shuang; Li, Hui-ping; Jia, Pin-hui; Song, Ming-jie; Di, Peng; Li, Wei
Abstract: Cisplatin ( cis -Dichlorodiammine platinum, CP), as the first-line chemotherapy drug of choice for many cancers such as urogenital system tumors and digestive tract tumors, also causes toxicity and side effects to the kidney. Previous studies have shown that Pulsatilla chinensis has significant anti-inflammatory and antioxidant activities, but the mechanism of cisplatin induced acute kidney injury (AKI) in vivo has not been thoroughly studied. The purpose of this study is to investigate the protective effect of pulchinenoside B4 (PB4), a representative and major component with a content of up to 10% in root of P. chinensis, on AKI induced by CP in mice. Our results indicated the significant protective effect of PB4 by evaluating renal function indicators, inflammatory factor levels and renal histopathological changes. In addition, PB4 may mainly act on NF-κB signaling pathway to reduce the levels of tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) in the kidney after CP exposure, thus exerting anti-inflammatory activity. Furthermore, PB4 regulated MAPK signaling pathway and its downstream apoptotic factors to inhibit the occurrence of apoptosis, such as Bax, Bcl-2, caspase 3 and caspase 9. Notably, the activations of caspase 3 induced by cisplatin were strikingly reduced in PB4-treated mice. Therefore, the above evidence suggested that PB4 is a potential renal protectant with significant anti-inflammatory and anti-apoptotic effects. Graphical abstract: Image 1 Highlights: PB4 alleviated renal function damage induced by CP in AKI mice. PB4 blocked the NF-κB signaling pathway and reduced the inflammatory level in mice. PB4 inhibited the MAPK signaling pathway and improved the level of apoptosis.